(untitled) (Research, Society and Development, 2022)
Introduction: Burnout Syndrome (BS) emerged in the 197’s and has three components: emotional, depersonalization and low professional achievement. Objective: To investigate, through the literature, what are the factors associated with Burnout Syndrome in teachers during the COVID-19 pandemic. Method: Integrative literature review, with a qualitative approach, exploratory and descriptive. The survey in the databases at LAT was carried out in MEDLINE and LIL through the VHL, and the portal accessed by Periódicos da Capes. The descriptors used were: “burnout”, “teachers” and “COVID-19”, crossed by the Boolean operator AND. Primary studies were included, available with full texts, between 2020 and 2021, in Spanish, English and Brazilian Portuguese. Review studies, articles not tested by peers, duplicate articles from the database, incomplete, and research that deviated from the theme and objective were excluded. Results and discussion: Initially, 22 articles were found. 21 were selected for analysis, where six composed the final review. The main factors related to SB or class activities factors, increase in meetings, lack of training, training room, excessive control conditions at work, increase of employees in local activities, transform the work environment, share with others in the family, between others. Final Considerations: It is essential that actions are developed in order to guarantee the professional satisfaction of teachers, either through psychological monitoring or through activities that help professional satisfaction in educational institutions.